(untitled) (Swiss Medical Weekly, 2013)
Aptamers are single-stranded deoxyribonucleic acid (DNA) or ribonucleic acid (RNA) oligonucleotides, which are able to bind their target with high selectivity and affinity. Owing to their multiple talents, aptamers combined with nanoparticles are nanosystems well qualified for the development of new biomedical devices for analytical, imaging, drug delivery and many other medical applications. Because of their target affinity, aptamers can direct the transport of aptamer-nanoparticle conjugates. The binding of the aptamers to the target “anchors” the nanoparticle-aptamer conjugates at their site of action. In this way, nanoparticle-based bioimaging and smart drug delivery are enabled, especially by use of systematically developed aptamers for cancer-associated biomarkers. This review article gives a brief overview of recent relevant research into aptamers and trends in their use in cancer diagnostics and therapy. A concise description of aptamers, their development and functionalities relating to nanoparticle modification is given. The main part of the article is dedicated to current developments of aptamer-modified nanoparticles and their use in cancer diagnostics and treatment. Summary and outlook The huge potential of aptamer-nanoparticle-based detection of cancer cells and biomedical in-vivo imaging has been shown, with some examples. Gold nanoparticles offer unique properties that make them ideal detection materials. Specifically, the colour change caused by their aggregation or disaggregation and connected to the aptamer-target binding reaction has been used in the development of assays and tests. The colour change can be processed even with the naked eye, without any device necessary [34]. This application is especially user-friendly and, in principle, comparable to the well-known pregnancy test. Point-of-care diagnostics based on this principle soon will easily find the way to commercialisation. Besides gold nanoparticles, other metal and magnetic nanoparticles, silica- or polymer-based nanoparticles and quantum dots are used. For combined diagnostic and medical use, the silica- or polymer-based nanoparticles have to be loaded with the drug. They can additionally include organic dyes for optical detection, just as functional groups for their conjugation with aptamers [52, 61]. Aptamer modified magnetic nanoparticles offer the possibility of magnetic resonance imaging as well as application of magnetic fluid hypothermia therapy [64]. Quantum dots extend optical detection methods in various directions. They are particular suitable for quantum dot-stimulated FRET-based (beacon) aptamer assays [61]. Aptamer-modified nanoparticles for medical applications are developed mostly for the detection of analytes, for biomedical in-vivo imaging and for in-vivo drug delivering. Merging nanoparticles with aptamers permits additional or enhanced medical tools for many biomedical applications by combination of the complementary outstanding properties of each. Nanoparticles that are suitable for detection and loading with drugs can be directed to the site of their action by use of the affinity and specificity of aptamers, which are conjugated to the nanoparticles or fixed on their surface. This is of great relevance in cancer therapy in particular. Most anticancer pharmaceuticals have destructive effects not only on the cancer cells, but also on healthy cells. Aptamers can facilitate cell-specific drug delivery in a selective manner to the sick cancer cells because of their binding specificity. This can enhance therapeutic effects and diminish adverse effects. Moreover, simultaneous in-vivodetection and therapy for cancer cells lowers the burden for cancer patients. However, the widespread phenomenon of possible nonspecific accumulation of nanoparticles in the liver, which is not caused by aptamer modification, must be taken into account. Methods for aptamer-based nanoparticle application have been developed, but mostly by use of a few aptamers. The development of more aptamers specific to cancer cells or marker proteins is urgently needed, especially for these applications. This is the precondition for provision of these new detection, imaging and therapy methods.